â€œULVAâ€ PENGEMBANGAN TEKNIK PENANDA ALAMI PADA BUDIDAYA ABALON (Haliotis squamata) - Permana, Gusti Ngurah; Rusdi, Ibnu; Wibawa, Gigih Satria; Setiabudi, Gede Iwan (JFMR (Journal of Fisheries and Marine Research), 2021)
"ULVA" NATURAL MARKING TECHNIQUES DEVELOPMENT IN ABALONE CULTURE (Haliotis squamata)Â  ByÂ  Gusti Ngurah Permana,, Ibnu Rusdia, Â Gigih Satria Wibawaa and Iwan SetyabudibTagging is used to obtain some information during the process of selecting and managing population of abalone shells, Haliotis squamata. This research was conducted to determine the natural marker method of abalone, (H. squamata). The samples were used of Â total length of the shell (initial average: 0.8 Â± 0.2 mm).Â  Seed tagging using the Ulva sp. performed by giving a sequence of feed at the age of: 2-3 months (Ulva sp.), 3-4 months (Gracilaria sp.), 5-6 months (Ulva sp.), 6-10 months (Gracillaria sp.) and control 2 months (Ulva sp.), 3-10 months (Gracilaria sp.). The results of this study indicated that the tagging of the seeds with the Ulva method has a same growth pattern in bothÂ  treatment and control (38.93 Â± 1.5 mm; 39.47 Â± 1.44 mm). The effectiveness of Ulva tagging is seen in toca color finder (TC. 4103 green) and (TC 8135 brown), more sharpen in treatment compared to control. Ulva tagging technology can be applied to abalone seeds to see the sequence of the green color on the shell.Â Â